2023
DOI: 10.3390/ijms24043597
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Human Accelerated Regions in Schizophrenia and Related Disorders: Where the Evolutionary and Neurodevelopmental Hypotheses Converge

Abstract: Schizophrenia is a psychiatric disorder that results from genetic and environmental factors interacting and disrupting neurodevelopmental trajectories. Human Accelerated Regions (HARs) are evolutionarily conserved genomic regions that have accumulated human-specific sequence changes. Thus, studies on the impact of HARs in the context of neurodevelopment, as well as with respect to adult brain phenotypes, have increased considerably in the last few years. Through a systematic approach, we aim to offer a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…These HAR genes have been suggested to have a vital role in human brain development (76) and may induce multiple brain disorders (77). As a previous review suggested (29), HARs are involved in the genetic signature of neurodevelopmental-related psychiatric disorders including schizophrenia. Accordantly, we found an association between the S-A epicenter axis of EOS and brain expression maps of HAR genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These HAR genes have been suggested to have a vital role in human brain development (76) and may induce multiple brain disorders (77). As a previous review suggested (29), HARs are involved in the genetic signature of neurodevelopmental-related psychiatric disorders including schizophrenia. Accordantly, we found an association between the S-A epicenter axis of EOS and brain expression maps of HAR genes.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis posits that these mental illnesses emerge as costly by-products of human evolution (27). For example, the human accelerate region (HAR) genes, i.e., the human-specific genes located in the accelerated diverging HARs between humans and chimpanzee ancestors (28), may harbor common genetic determinants shared across different psychiatric disorders (29). Notably, the availability of whole-brain gene expression atlases from the Allen Human Brain Atlas ([AHBA]; http://human.brain-map.org) microarray dataset (30) offers an unprecedented chance to bridge the brain connectome and microscale gene transcriptomes (31).…”
Section: Introductionmentioning
confidence: 99%
“…Through a neuroimaging genetic approach, we have evaluated the SZ’s polygenic burden of human-specific evolutionary markers such as HARs on brain-based phenotypes closely related to the pathophysiology of the disorder. Although studies on HARs are an emerging field, as a recent review by our group highlights 57 , and the expression profiles of HARs-brain genes have been studied in relation to brain structural changes across different psychiatric disorders 48 , our study is the first to assess the effect of HARs genetic variability on brain cortical measures in patients with SZ and healthy controls. These analyses provide evidence of the impact of foetal active regulatory HARs on the cortical surface area of different brain regions in patients with SZ.…”
Section: Discussionmentioning
confidence: 99%
“…After a first study had identified and partially characterized a "human accelerated region" (HAR) [42], further HARs were investigated and indeed, as one important discovery, their proximity to neuropsychiatric disease genes was revealed [39,[148][149][150][151][152][153][154]. Since many HAR-associated genes are regulators and hubs in transcriptional networks, their differential expression would affect many other genes and cellular processes, suggesting outsized effects caused by noncoding HAR mutations.…”
Section: Primate/human-specific Ncrnas In Neural/neuroimmune Cells An...mentioning
confidence: 99%